Ir-catalysed asymmetric allylic substitutions with cyclometalated (phosphoramidite)Ir complexes - resting states, catalytically active (π-Allyl)Ir complexes and computational exploration - Raskatov, Jevgenij; Spiess, Stephanie; Gnamm, Christian; Brödner, Kerstin; Rominger, Frank; Helmchen, Günter (Chemistry - a European journal, 2010)
Mechanistic aspects of allylic substitutions with iridium catalysts derived from phosphoramidites by cyclometalation were investigated. The determination of resting states by 31P NMR spectroscopy led to the conclusion that the cyclometalation process is reversible. A novel, one-pot procedure for the preparation of (π- allyl)Ir complexes was developed, and these complexes were characterised by X-ray crystal structure analyses and spectral data. They are fully active catalysts of the allylic substitution reaction. DFT calculations on the allyl complexes, transition states of the allylic substitution and product olefin complexes gave further mechanistic insight.
Gesehen am 10.05.2023